Acetylcholinesterase inhibitor treatment alleviated cognitive impairment caused by delayed encephalopathy due to carbon monoxide poisoning: Two case reports and a review of the literature. Issue 8 (February 2017) - Yanagiha, Kumi; Ishii, Kazuhiro; Tamaoka, Akira
Abstract: Introduction: Delayed encephalopathy due to carbon monoxide (CO) poisoning can even occur in patients with mild symptoms of acute CO poisoning. Some cases taking conventional hyperbaric oxygen (HBO) therapy or steroid-pulse therapy may be insufficient, and AchEI may be effective. Patient Concerns and Diagnoses: We report two cases of delayed encephalopathy after acute CO poisoning involving two women aged 69 (Case 1) and 60 years (Case 2) whose cognitive function improved with acetylcholinesterase inhibitor (AchEI) treatment. Delayed encephalopathy occurred 25 and 35 days after acute CO poisoning in Case 1 and Case 2, respectively. Both patients demonstrated cognitive impairment, apathy, and hypokinesia on admission. Interventions and Outcomes: Although hyperbaric oxygen therapy did not yield any significant improvements, cognitive dysfunction improved substantially. This was evidenced by an improved Mini-Mental State Examination score ffom 9 to 28 points in Case 1 and an improved Hasegawa's dementia rating scale score from 4 to 25 points in Case 2 after administration of an AchEI. In Case 1, we administered galantamine hydrobromide, which was related with improved white matter lesions initially detected on brain magnetic resonance imaging. However, in Case 2 white matter lesions persisted despite AchEI treatment. AchEI treatment may result in improved cognitive and frontal lobe function by increasing low acetylcholine concentrations in the hippocampus and frontal lobe caused by decreased nicotinic acetylcholine receptor levels in delayed encephalopathy after CO poisoning. Conclusion: Physicians should consider AchEIs for patients demonstrating delayed encephalopathy due to CO poisoning.